Aminopropyltrimethoxysilane-functionalized boron nitride nanotube based epoxy nanocomposites with simultaneous high thermal conductivity and excellent electrical insulation. Issue 42 (22nd October 2018) - Zhang, Chi; Huang, Rongjin; Wang, Yongguang; Wu, Zhixiong; Guo, Shibin; Zhang, Hua; Li, Jian; Huang, Chuanjun; Wang, Wei; Li, Laifeng
Abstract : An ideal dielectric epoxy nanocomposite with high thermal conductivity is successfully fabricated utilizing aminopropyltrimethoxysilane-functionalized BNNTs. Abstract : Insulating polymeric materials with excellent thermal and dielectric properties are highly promising for thermal management applications in future energy systems. However, a well-acknowledged problem is that traditional polymeric composites usually suffer from either low thermal transfer efficiency or high dielectric loss, failing to meet the requirements for simultaneous properties of high thermal conductivity and high electrical insulation. In this work, utilizing aminopropyltrimethoxysilane-functionalized boron nitride nanotubes (BNNT-APS) as fillers, an ideal dielectric epoxy nanocomposite is successfully fabricated. At a low BNNT loading of 10 wt%, the nanocomposites demonstrate a 650% thermal conductivity enhancement at both room temperature and cryogenic temperatures with the preservation of a low dielectric constant and dielectric loss. In addition, a 20% reduction of the coefficient of thermal expansion (CTE) at cryogenic temperatures is achieved at the same time. The superiority of the designed nanocomposites is suggested to stem from the outstanding intrinsic properties of BNNTs, effective surface modification by APS molecules, and low interfacial thermal resistance.